2021
DOI: 10.1002/mp.14917
|View full text |Cite
|
Sign up to set email alerts
|

Does FLASH deplete oxygen? Experimental evaluation for photons, protons, and carbon ions

Abstract: Purpose To investigate experimentally, if FLASH irradiation depletes oxygen within water for different radiation types such as photons, protons, and carbon ions. Methods This study presents measurements of the oxygen consumption in sealed, 3D‐printed water phantoms during irradiation with x‐rays, protons, and carbon ions at varying dose rates up to 340 Gy/s. The oxygen measurement was performed using an optical sensor allowing for noninvasive measurements. Results Oxygen consumption in water only depends on do… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(77 citation statements)
references
References 23 publications
2
64
0
Order By: Relevance
“…The fundamental physicochemical mechanisms underlying the FLASH effect are currently under investigation; one hypothesis implicating transient local oxygen depletion was first proposed nearly 40 years ago 43,44 . However, direct measurements of such depletion in vivo are difficult to obtain, 45,46 and so most of the evidence to date has been collected via indirect measurements. As one example, reductions in hydrogen peroxide (H 2 O 2 ) in FLASH‐irradiated water have been reported 35 .…”
Section: Flash: Preclinical Investigations Using Electron Beamsmentioning
confidence: 99%
“…The fundamental physicochemical mechanisms underlying the FLASH effect are currently under investigation; one hypothesis implicating transient local oxygen depletion was first proposed nearly 40 years ago 43,44 . However, direct measurements of such depletion in vivo are difficult to obtain, 45,46 and so most of the evidence to date has been collected via indirect measurements. As one example, reductions in hydrogen peroxide (H 2 O 2 ) in FLASH‐irradiated water have been reported 35 .…”
Section: Flash: Preclinical Investigations Using Electron Beamsmentioning
confidence: 99%
“…9 The mechanism of FLASH radiotherapy in sparing normal tissues is not well understood; several hypotheses based on basic radiation physics and chemistry of reactive oxygen species (ROS) and tumor versus normal cell redox metabolism have been proposed in the literature to explain the FLASH effect. [10][11][12][13][14][15] FLASH radiation beams have been achieved using x-rays in a research synchrotron facility, 6 electrons by using medical linear accelerators, [3][4][5]16,17 protons by clinical isochronous cyclotrons [18][19][20][21][22] and a clinical synchrocyclotron. 23 In our previous work, 23 we demonstrated the feasibility of delivering proton beams at a FLASH dose rate in a pristine Bragg peak pattern using a clinical synchrocyclotron as a first step toward realizing an experimental platform for preclinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…The safety and feasibility of treating a first human patient with FLASH radiotherapy was shown in 2019 9 . The mechanism of FLASH radiotherapy in sparing normal tissues is not well understood; several hypotheses based on basic radiation physics and chemistry of reactive oxygen species (ROS) and tumor versus normal cell redox metabolism have been proposed in the literature to explain the FLASH effect 10‐15 …”
Section: Introductionmentioning
confidence: 99%
“…The implied oxygen depletion detected in the previous model implementation (dashed lines in Figure 3 ) was based on a dose-rate independent oxygen depletion rate constant , as suggested by Petersson et al [ 8 ]. Cao et al (and others [ 19 ]) observed an increased amount of oxygen depleted at SDR (for Cao et al at about 0.1 Gy/s) in comparison to uHDR ( Figure 3 —left panel). To account for this effect, we used an empirical parametrization of g over the applied dose rate (Equation (12)), using the three phenomenological parameters and .…”
Section: Resultsmentioning
confidence: 63%